Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1997
DOI: 10.1007/bf00048446
|View full text |Cite
|
Sign up to set email alerts
|

Review of the dynamics in the Kirkwood gaps

Abstract: The study of mean motion resonance dynamics was motivated by the search for an explanation for the puzzling problem of the Kirkwood gaps. The most important contributions in this field within the last 32 years are reviewed here. At the beginning of that period, which coi'ncides with the first long-term numerical investigations of resonant motion, different hypotheses (collisional, gravitational, statistical and cosmological) to explain the origin of the gaps were still competing with each other. At present, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(23 citation statements)
references
References 64 publications
(90 reference statements)
0
23
0
Order By: Relevance
“…The 3:l resonance is located at 2.5 AU. Wisdom (1985) showed that the resonance pushes all particles to Mars-crossing, and some to Earth-crossing orbits; later work (see Moons, 1997 for a review) showed that the resonance can pump particle eccentricities nearly to unity. Even at e = I , particles in the resonance do not quite cross the orbit of Jupiter; and in any case, the resonance protects them from Jovian close encounters.…”
Section: The 3: 1 Resonancementioning
confidence: 98%
“…The 3:l resonance is located at 2.5 AU. Wisdom (1985) showed that the resonance pushes all particles to Mars-crossing, and some to Earth-crossing orbits; later work (see Moons, 1997 for a review) showed that the resonance can pump particle eccentricities nearly to unity. Even at e = I , particles in the resonance do not quite cross the orbit of Jupiter; and in any case, the resonance protects them from Jovian close encounters.…”
Section: The 3: 1 Resonancementioning
confidence: 98%
“…Despite this lack of close planetary encounters to explain this particle's evolution onto a main-belt-like orbit, we note that besides having the largest T J,s of the eight particles, placing it very close to the ostensible boundary between asteroids and comets at the outset of the integrations, it begins (and ends) very close to the strongly chaotic 2:1 MMR with Jupiter, known for being capable of causing large fluctuations in eccentricities (cf. Murray, 1986;Moons, 1997;Nesvorný & Ferraz-Mello, 1997), and may also be subject to secular resonances (cf. Williams & Faulkner, 1981) and threebody MMRs (cf.…”
Section: Detailed Orbital Evolution Analysismentioning
confidence: 99%
“…Planetary mean motion resonances may also exist in exoplanetary systems (Marcy et al 2001;Lee & Peale 2002;Fabrycky et al 2014;Petigura et al 2015;Nelson et al 2016;Mills et al 2016). Furthermore, unstable mean motion resonances are also of great significance; for example, the Kirkwood Gaps in the asteroid belt are linked to the unstable and chaotic MMRs with Jupiter (Moons 1996), and the stability of our planetary system itself is intimately related to the role of MMRs (Murray & Holman 1999) The phase space structure near MMRs is quite complex, and there is a considerable literature on their mathematical analysis. The planetary three body problem, with m 1 m 2 , m 3 , is the usual starting point of such studies.…”
Section: Introductionmentioning
confidence: 99%